Aspectos biológicos de Heterotermes tenuis (Isoptera Rhinotermidae) em cana-de-açúcar - Campos, Maria Bernadete Silva de (Universidade Federal de São Carlos, 2004)
The main objectives were: to study at laboratory some biological aspects the biology of Heterotermes tenuis, by stablishing colonies with couples collected in the field, foraging behavior and the intraspecific agonistic behavior among individuals from different places in area sugarcane, collected by baits. The stablishment of colonies was studied from September/2002 to December/2003, with the installation of 400 baits in of 10.000 m2 sugarcane area, to collect the couples. The collected couples were removed and aconditioned in plastic flasks containing humidified soil and food and maintained in room at 28°C ± 2°C, 70% RU and 12 hours of photophase. Biological studies was systematicaly the colonies for counting alive couples, presence and number of eggs, breeds (workers and soldiers). The couples showed a period of 29 days before oviposition and a number of five eggs/ colony in the first oviposition, in average. The egg measures were 0.68 mm length and 0.36 mm width. The first workers appeared 53 days after the formation of the couples, and the number was four workes/colony. The first soldiers appeared 127 days after the formation of the couples, with an average of 1 soldier/colony. Foraging behavior was studied from 1999, April to 2003, December with the installation of 27 baits in three different places with nine points each. Monthly the baits were removed and a new one were placed. Baits with termites present were carried to laboratory for individuals counting. It was observed that there were significant variances in the foraging activity according to rain precipitation and environmental temperature variations and it was affected, as well, by development cycle and growth of the colony. The maximum foraging activity occures in the autumn and the agricultural pratices as plowing and furrowing for new planting promote a drastic foraging activity redutions in the subsequent years. Intraspecific agonistic behavior of H. tenuis was studied by confrontation tests between places and different points. In each confrontation 20 workers plus two soldiers were placed in a transparent plastic flask (7,0 cm of height x 4,5 cm of diameter) with bottom covered by filter paper and a square of humidified fiberboard (4 cm2) . The evaluations were done 48 hours after the confrontation by counting dead individuals. It was verified that there is intra-specific agonistic behavior in H. tenuis and by means that behavior different colonies can be distinguished and its forraging areas can be delimited in sugarcane areas.
Keywords: Inseto; Cupim subterrâneo; Cana-de-açucar; Forrageamento; Comportamento agonístico; CIENCIAS AGRARIAS::AGRONOMIA